Developing The Search, Solve, Create, And Share (SSCS) - Based Student Worksheets In Biology Learning - M Amrullah Effendi; Hasruddin; Fauziyah Harahap (Publikasi Indonesia, 2021)
The SSCS learning that is collaborated with student worksheets can enhance students more actively in learning because this process can facilitate students in finding and building knowledge to solve problems. The method applied a Research and Development (R&D) adapted from Borg and Gall model. This study was only carried out until the development stage. The results showed that the SSCS-based student worksheets according to material experts containing the aspects of content eligibility of 85.19% with an excellent/eligible category, the presentation eligibility of 85% with an excellent/eligible category, and the SSCS components of 85.26% with an excellent/eligible category. Meanwhile, according to design experts containing the aspects of cover design of 90% with an excellent/eligible category, the cover typography of 100% with an excellent/eligible category, the content design of student worksheet of 87.50 with an excellent/eligible category, and the content illustration of student worksheet of 81.25% with an excellent/eligible category. Based on the teachers’ responses showed an excellent/eligible category, with total score of the teachers’ assessment of 92.17%. The results of students’ responses based on individual tests of 78.13% with an excellent category, small group tests of 78.24% with an excellent category as well as the limited field tests of 81.48% with an excellent category.